Beltzville Lake Condition Report Dam, Outlet Works & Spillway, Periodic Inspection Report Number 5, September 1974, Lehigh River Basin, Pohopoco Creek, Pennsylvania. - ARMY ENGINEER DISTRICT PHILADELPHIA PA (1975)
This report summarized the results of the fifth periodic inspection of Beltzville Dam which is located on Pohopoco Creek in the Lehigh River Basin. This inspection was held on Sept. 16-17, 1974 by members of the Philadelphia District and the North Atlantic Division of the U.S. Army Corps of Engineers. No major areas of concern were noted by the inspection team as the overall condition of the project was considered excellent. Instrumentation data, as well as, the results of the visual inspection of the spillways, embankment, stilling basin, intake tower and drainage areas were given. (Author)